Karakteristik Hidrologi Tanah pada Berbagai Tingkatan Umur Tanaman Penghijauan di Desa Pelaga, Kecamatan Petang Kabupaten Badung - NI KOMANG HARI PADMAYANI; I NYOMAN SUNARTA; WIYANTI WIYANTI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Characteristics of Soil Hydrology At Various Age Levels of Reforestation In Pelaga Vilage Petang Ditrict, Badung Regency Nowadays many areas are experiencing drought during the dry season and flooding during the rainy season, so the water is no longer available throughout the year due to an imbalance of the hydrological cycle. The imbalance is caused by two factors: natural factors and management factors. Reforestation plants are expected to have the function of forests as an effective natural run off control. The purposes of this research were to know the difference of hydrological characteristics at several age levels reforestation and to determine the role of plant ages in improving soil hydrological properties at Pelaga vilage. The data was analysed with descriptive quantitative method..The results from this research of characterized the hydrological at various age levels of reforestation was increased fluctuatingly. Available water on reforestation 1,2,3,4,5 years old and controls respectively 14.75%, 12.07%, 14.90%, 13.98%, 15.88%, and 12.22%. The highest characteristics of soil hydrology was achieve in the reforestation area of the five years old or after harvest was 15.88%. The increasing levels of water available between the ages of five years over control was 29.95%.